ESTIMASI KURVA REGRESI SPLINE PADA DATA LONGITUDINAL DENGAN METODE KUADRAT TERKECIL - Toto Hermawan (Intersections, 2020)
This article examines the estimation of spline regression, especially its use in longitudinal data. Longitudinal data is data obtained based on observations made as many as n objects that are independent with each object being repeatedly observed in different time periods and between observations in the same object are dependent besides longitudinal data is data that can distinguish the diversity of responses caused by The regression curve of the spline was estimated using the least squares. It can be seen that the estimation of the spline regression curve for longitudinal data is a class of linear estimation in response observations and is highly dependent on the knots point k1,k2,...,Kn